Bridging markers defining the map position of X linked hypophosphataemic rickets. Issue 12 (December 1987) - Thakker, R V; Read, A P; Davies, K E; Whyte, M P; Weksberg, R; Glorieux, F; Davies, M; Mountford, R C; Harris, R; King, A
Abstract : Hypophosphataemic rickets is commonly an X linked dominant hereditary disorder associated with a renal tubular defect in phosphate transport and bone deformities. The gene causing this disorder has been mapped to Xp22.31—-p21.3 by using cloned human X chromosome sequences identifying restriction fragment length polymorphisms (RFLPs) in linkage studies of affected families. The hypophosphataemic rickets gene locus (HPDR) was previously mapped distal to the X linked polymorphic locus DXS41 (99.6) but its position in relation to the distal loci DXS43 (D2) and DXS85 (782) was not established. In order to obtain a precise mapping of the disease locus in relation to these genetic loci, additional affected families informative for these X linked markers have been investigated. The combined results from the two studies have established linkage with the loci DXS41 (99.6) and DXS43 (D2); peak lod score for DXS41 (99.6) = 7.35, theta = 0.09, and peak lod score for DXS43 (D2) = 4.77, theta = 0.16. Multilocus linkage analysis mapped the hypophosphataemic rickets gene distal to the DXS41 (99.6) locus and proximal to the DXS43 (D2) locus, thereby revealing two bridging genetic markers for the disease.